The Subtle Line that Differentiates between Ethnic Cleansing and Genocide - Raihany, Farras Audia; Bernard, Yulian; Hidajaty, Hidajaty (Andalas Law Journal, 2023)
The Bosnian genocide refers to the Srebrenica massacre and other acts of ethnic cleansing during the Bosnian War of 1992–1995. This study was conducted using normative-empirical methods combining juridical and sociological elements that focused on implying the elements in the body of Article 6 of Rome Statute 1998 with the actual events that occurred in the Bosnian Genocide cases. The study aimed to analyze the distinction between ethnic cleansing and genocide based on its execution and planning, particularly in relation to the Rome Statute of 1998, which established the International Criminal Court (ICC). The study found that ethnic cleansing seeks to expel a group from a specific area, while genocide aims to physically destroy entire racial, ethnic, or religious groups. Ethnic cleansing focuses on achieving ethnic homogeneity, while genocide seeks the complete annihilation of a group. After the establishment of the ICC in 2002, ethnic cleansing became explicitly covered under international law, alongside genocide, crimes against humanity, and war crimes.